Bis-Cyclic Guanidines as a Novel Class of Compounds Potent against Clostridium difficile - Li, Chunhui (ChemMedChem, 2018)
Clostridium difficile infection (CDI) symptoms range from diarrhea to severe toxic megacolon and even death. Due to its rapid acquisition of resistance, C. difficile is listed as an urgent antibiotic-resistant threat, and has surpassed methicillin-resistant Staphylococcus aureus (MRSA) as the most common hospital-acquired infection in the USA. To combat this pathogen, a new structural class of pseudo-peptides that exhibit antimicrobial activities could play an important role. Herein we report a set of bis-cyclic guanidine compounds that show potent antibacterial activity against C. difficile with decent selectivity. Eight compounds showed high in vitro potency against C. difficile UK6 with MIC values of 1.0 μg mL−(1), and cytotoxic selectivity index (SI) values up to 37. Moreover, the most selective compound is also effective in the treatment of C. difficile-induced disease in a mouse model of CDI, and appears to be a very promising new candidate for the treatment of CDI.